2005
DOI: 10.1002/bit.20620
|View full text |Cite
|
Sign up to set email alerts
|

Strain stability in biological systems treating recalcitrant organic compounds

Abstract: The availability of molecular probing technology in recent years has facilitated investigation of microbial community composition during bio-treatment of organic wastes. Particularly, it has allowed the study of microbial culture stability and correlation between stability and treatment performance. However, most studies to date have only addressed mixed cultures and there is limited information regarding single strain stability. Here we have investigated the microbial community dynamics in two bioreactors, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…This strain has been studied in several bioreactor configurations for the treatment of MCB contaminated streams (Ferreira Jorge and Livingston, 2000;Haigler et al, 1992;Oliveira and Livingston, 2003). However, the latest study reported its disappearance from a functionally stable bioreactor (Emanuelsson et al, 2005). Similar cases of species out-competition and succession during biodegradation processes have been reported (MassolDeya et al, 1997;Springael et al, 2002;Von Canstein et al, 2001).…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…This strain has been studied in several bioreactor configurations for the treatment of MCB contaminated streams (Ferreira Jorge and Livingston, 2000;Haigler et al, 1992;Oliveira and Livingston, 2003). However, the latest study reported its disappearance from a functionally stable bioreactor (Emanuelsson et al, 2005). Similar cases of species out-competition and succession during biodegradation processes have been reported (MassolDeya et al, 1997;Springael et al, 2002;Von Canstein et al, 2001).…”
Section: Introductionmentioning
confidence: 82%
“…The MCB concentration in the biomedium and the biomass concentration were analysed as previously described (Emanuelsson et al, 2005). Chloride concentration was analysed by ion chromatography (Dionex DX 120 with an IonPAC AS114 4 mm  250 mm column; Camberley, UK).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations